Comportamiento del fenotipo de las plantas de café (Coffea arabica) con la aplicación de bioestimulantes en diferentes etapas de crecimiento - Benecio Cunalata, Angel Jair (2024)
Coffee productivity stands out as one of the most relevant in global agriculture. In Ecuador, coffee production represents a crucial agricultural activity, particularly in areas such as Loja and Manabí. Approaches to the phenotype of coffee plants with the application of biostimulants at different growth stages and the efficacy of different types of biostimulants have emerged as an innovative strategy to improve the yield and quality of coffee crops. For this document, information is gathered from current documents, research articles, virtual libraries and websites to help present the opinions and ideas of actors that allow research developments. Relevant topics were identified in the behavior of the phenotype of coffee plants with the application of biostimulants at different growth stages. This study indicates that the use of biostimulants has a significant positive effect on the phenotypic characteristics of coffee plants at different growth stages. Research has shown that biostimulants can be an effective tool to improve the productivity of coffee crops. Plants treated with biostimulants develop a stronger root system and a greater number of leaves and stems, from the nursery stage to production. By identifying the growth stages where biostimulants are most effective, the results can influence agricultural policies and the formulation of agronomic management strategies that promote more sustainable and efficient practices in coffee production.